Corporate Social Responsibility disclosure: A study on audit committee, audit quality, and company size - Rahayu, Yurik Prastika; Yendrawati, Reni (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This study aims to determine the effects of audit committees, audit quality, and company size on Corporate Social Responsibility (CSR) disclosure. The research population comprises ASEAN companies in the energy sector listed in Osiris between 2022 and 2023. Purposive sampling was used, resulting in 66 sample companies. Secondary data from Osiris were processed and analyzed using panel data regression. The selected data is the Random Effect Model (REM). The findings show that company size has a positive and significant effect on corporate social responsibility disclosure because large companies face higher pressure from stakeholders to increase transparency and accountability, including in terms of CSR disclosure. However, the audit committee and audit quality show no influence. The audit committee has no effect on CSR disclosure, possibly because the audit committee is only a formality to comply with regulations without really supervising and encouraging CSR disclosure. Audit quality has no effect on CSR disclosure because the main focus of the audit is likely still on financial statements, and high audit costs are required to verify the disclosure.